Facile synthesis and biological evaluation of tryptamine-piperazine-2, 5-dione conjugates as anticancer agents. Issue 45 (17th August 2021) - Meng, Jiang-Ping; Li, Shi-Qiang; Tang, Yan; Xu, Zhi-Gang; Chen, Zhong-Zhu; Gao, Li-Xia
Abstract : A series of tryptamine-piperazine-2, 5-dione conjugates derivatives was designed and synthesized via Ugi cascade reaction. The discovery of compound 6h may provide a new avenue for pancreatic cancer drug discovery. Abstract : A facile and efficient route to synthesize N-heterocyclic fused tryptamine-piperazine-2, 5-dione conjugates was developed via a post-Ugi cascade reaction. The targeted compounds were prepared by means of a mild reaction and simple operation procedure, which could be applied to a broad scope of starting materials. Compound 6h was demonstrated to induce significant growth inhibition of AsPC-1 and SW1990 human pancreatic cancer cell lines (IC50 = 6 ± 0.85 μM). Our protocol allows for the construction of a structurally diverse compound library and paves a new avenue for the discovery of pancreatic cancer drug candidates.